Babylonian disputation poems : with editions of the series of the poplar, palm and vine, the series. of the spider, and the story of the poor, forlorn. - Jimnez, Enrique. (Culture and History of the Ancient Near East, 2017)
In The Babylonian Disputation Poems Enrique Jiménez studies a group of ancient Babylonian poems that feature discussions between animals and trees. Using intertextual parallels and comparison with similar works in other literatures, he espouses a new classification of the Babylonian disputation poems as parodies. After examining neighboring traditions of literary disputation, he argues that the Babylonian poems influenced them, and that some may have been translated from Akkadian to Aramaic, from Aramaic and Syriac to Arabic. In addition, The Babylonian Disputation Poems provides editions of several previously unpublished Babylonian disputations, such as Palm and Vine and the Series of the Spider . It also offers the first edition of the latest known Babylonian fable, The Story of the Poor, Forlorn Wren .